Enzymatic approach to cascade synthesis of bis(indolyl)methanes in pure water. Issue 18 (16th March 2020) - Fu, Yajie; Lu, Zeping; Fang, Ke; He, Xinyi; Xu, Huajin; Hu, Yi
Abstract : TLIM: lipase from Thermomyces lanuginosus immobilized on particle silica gel. Abstract : A mild, efficient, and green protocol was developed for the synthesis of bis(indolyl)methanes catalyzed by lipase TLIM through the cascade reactions of indole with aldehydes in pure water. This methodology offers many superiorities such as excellent yields, wide substrate range, simple procedure, reusable and minimal amount of catalyst, and the ability to be scaled up.